Wide-Detector Computed Tomography for Evaluating the Effectiveness of Microsurgical Autotransplantation of Tissue Complexes in the Urogenital Region - I. O. Shchekoturov; R. F. Bakhtiozin; A. L. Istranov; N. S. Serova; O. A. Mkhitaryan; M. R. Ibregimova (Вестник рентгенологии и радиологии, 2020)
Objective: to demonstrate the possibilities and advantages of wide-detector computed tomography for performing dynamic studies and evaluating the effectiveness of microsurgical autotransplantation of tissue complexes in the urogenital region, by using a perfusion computed tomography and dynamic voiding computed cystourethrography.Subjects and methods. This investigation enrolled 36 patients with different urogenital diseases, who were examined using a wide-detector computed tomographic scanner and the procedures of dynamic perfusion computed tomography and dynamic voiding computed cystourethrography.Results. Perfusion examination revealed that none of the patients had hypoperfused areas of autografts, which suggests their good engraftment. Dynamic voiding computed cystourethrography estimated the width of the urethral lumen in all segments and identified the regions of its greatest narrowing and their extension. Computed uroflowmetry was scheduled for all patients.Conclusion. The advantages of wide-detector systems with their unique properties made it possible to apply them in the new area – in planning and evaluating the effectiveness of the microsurgical reconstruction of the urogenital region, by obtaining additional, previously unavailable diagnostic information.